2002
DOI: 10.1099/00221287-148-7-2215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Escherichia coli growth by acetic acid: a problem with methionine biosynthesis and homocysteine toxicity

Abstract: The mechanism by which methionine relieves the growth inhibition of Escherichia coli K-12 that is caused by organic weak acid food preservatives was investigated. In the presence of 8 mM acetate the specific growth rate of E. coli Frag1 (in MacIlvaine's minimal medium pH 6 0) is reduced by 50 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
255
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(264 citation statements)
references
References 37 publications
8
255
0
1
Order By: Relevance
“…These SCFAs inhibit Escherichia coli (E. coli) and Salmonella spp. growth in vitro (31) and may impair growth by their effects on pathways, resulting in methionine depletion and homocysteine accumulation (32). The cecal pH and SCFA profiles of mice that consumed this BFMP had a clear growth-inhibitory effect on the colitogenic Enterobacteriaceae of T-bet −/− Rag2 −/− mice in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These SCFAs inhibit Escherichia coli (E. coli) and Salmonella spp. growth in vitro (31) and may impair growth by their effects on pathways, resulting in methionine depletion and homocysteine accumulation (32). The cecal pH and SCFA profiles of mice that consumed this BFMP had a clear growth-inhibitory effect on the colitogenic Enterobacteriaceae of T-bet −/− Rag2 −/− mice in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the cytoplasmic pH of the bacterial cell which in turn affects the purine bases (Choi et al, 2000) resulting in denaturing essential enzymes inside the cell (Roe et al, 2002), ultimately leading to the death of bacteria. Gantois et al (2006) reported that when Salmonella spp.…”
Section: Direct Bactericidal Effect Of Sodium Butyratementioning
confidence: 99%
“…Finally, genes in a putative operon orthologous to microbial methionine transporters (CAC0984-CAC0986) were differentially upregulated after acetate stress. Studies in E. coli have shown that acetate inhibition at 8-33 mM concentration can be relieved by the addition of methionine (Han et al, 1993;Roe et al, 2002). A result of acetate stress is accumulation of the toxic intermediate homocysteine (Roe et al, 2002).…”
Section: Differential Expression Of Amino Acid Biosynthesis and Transmentioning
confidence: 99%
“…Studies in E. coli have shown that acetate inhibition at 8-33 mM concentration can be relieved by the addition of methionine (Han et al, 1993;Roe et al, 2002). A result of acetate stress is accumulation of the toxic intermediate homocysteine (Roe et al, 2002). In E. coli, homocysteine can perturb synthesis of branched-chain amino acids (Tuite et al, 2005).…”
Section: Differential Expression Of Amino Acid Biosynthesis and Transmentioning
confidence: 99%
See 1 more Smart Citation